Uji tarik komposit serat pandan alam sebagai komponen material bahan pengganti alternatif aluminium - Bawono, A.; Suroso, I.; Utami, N. (Universitas Mataram, 2023)
Seaplanes are aircraft that can land in the waters, this can be done because seaplanes have floaters. Floaters have a role so that the aircraft can float on the water. However, due to the fairly frequent interaction with water, it is necessary to have anti-corrosion treatment, this is because the use of metal as the basic material for making floaters is still dominant. Corrosion can be minimized by using composites as the constituent material. Making composites that can use fibres from nature can also be done such as the use of thorn pandanus fibres so that it will add more material value. In terms of mechanical strength, it is necessary to test to find out how strong the composite material of thorn pandan fibres is. In this study, composite manufacturing was carried out using the vacuum bagging method. The variation for fibre treatment is the duration of soaking time in 3 types of solutions, namely seawater, household wastewater, and river water. Material testing uses tensile tests. The results of tensile show that the relationship of immersion time to tensile strength in household wastewater is the best, all graphs tend to rise as the duration of immersion time increases.